On Some Lk-Finite-Type Euclidean Hypersurfaces. (6th September 2012) - Mohammadpouri, Akram; Kashani, S. M. B.
Abstract : We study some L k -finite-type Euclidean hypersurfaces. We classify L k -1-type Euclidean hypersurfaces and L k -null-2-type Euclidean hypersurfaces with at most two distinct principal curvatures. We also prove that, under some mild restrictions, there exists no L k -null-3-type Euclidean hypersurface.